2018
DOI: 10.1177/0273475318810335
|View full text |Cite
|
Sign up to set email alerts
|

Attracting Students to Sales Positions: The Case of Effective Salesperson Recruitment Ads

Abstract: Given the recent proliferation in sales programs, business colleges face a new set of challenges. Sales competencies are changing rapidly, and firms struggle with identifying and attracting sales candidates on campus. Therefore, it is important that we understand needed competencies and how the content of job advertisements may differentially appeal to various student populations. To do so, we develop a conceptual model, based on signaling theory, that focuses on how students formulate their intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…A sizable increase in the articles related to the perception of sales as a career path is evident in the sample. Recent articles survey student populations across the globe to explore the impact on student intent to pursue a sales career based on student traits including culture across seven nations (Fournier et al, 2014; Karakaya et al, 2014), school major (Deeter-Schmelz et al, 2018) and ethical control (Bush et al, 2014). The literature also investigates the impact of classroom interventions on student perception of sales.…”
Section: Discussion Of General Resultsmentioning
confidence: 99%
“…A sizable increase in the articles related to the perception of sales as a career path is evident in the sample. Recent articles survey student populations across the globe to explore the impact on student intent to pursue a sales career based on student traits including culture across seven nations (Fournier et al, 2014; Karakaya et al, 2014), school major (Deeter-Schmelz et al, 2018) and ethical control (Bush et al, 2014). The literature also investigates the impact of classroom interventions on student perception of sales.…”
Section: Discussion Of General Resultsmentioning
confidence: 99%
“…Job adverts can signal organisational commitment in developing the young inexperienced workforce (Moore and Khan, 2020). However, adverts can also deter applicants through the language used and the focus of the advert (Deeter-Schmelz et al , 2020; Protsch, 2017; Wofford and Smith, 2022). An illustration of the importance of ethical recruitment processes is highlighted in a qualitative study of apprenticeships in Switzerland by Goastellec and Ruiz (2015) who found that the criteria used to identify candidates tend to reproduce inequalities by using a “hidden curriculum” during the recruitment process, based on soft skills, used to identify the “right apprentice”.…”
Section: Literaturementioning
confidence: 99%
“…Sales professions can be a good opportunity to many graduating students because of the high request from the industry. As a result, it is the responsibility of business educators to enlighten students about job prospects in sales (Deeter-Schmelz et al 2020).…”
Section: Introductionmentioning
confidence: 99%